Placental syncytiotrophoblast-derived extracellular vesicles carry active NEP (neprilysin) and are increased in preeclampsia - Gill, M; Motta-Mejia, C; Kandzija, N; Cooke, W; Zhang, W; Cerdeira, S; Bastie, C; Redman, C; Vatish, M (American Heart Association, 2019)
NEP (neprilysin) is a widely expressed membrane-bound metalloprotease, which binds and cleaves a variety of peptides including vasodilators, natriuretics, and diuretics. Higher levels of NEP result in hypertension—a cardinal feature of the placental disease preeclampsia. Syncytiotrophoblast-derived extracellular vesicles (EVs), comprising microvesicles and exosomes, are released into the peripheral circulation in pregnancy and are postulated as a key mechanism coupling placental dysfunction and maternal phenotype in preeclampsia. We aimed to determine whether higher levels of active NEP are found in syncytiotrophoblast-derived EVs in preeclampsia compared with normal pregnancy. Using immunostaining and Western blotting, we first demonstrated that NEP levels are greater not only in preeclampsia placental tissue but also in syncytiotrophoblast-derived microvesicles and exosomes isolated from preeclampsia placentas (P<0.05, n=5). We confirmed placental origin using antibody-coated magnetic beads to isolate NEP-bound vesicles, finding that they stain for placental alkaline phosphatase. NEP on syncytiotrophoblast-derived EVs is active and inhibited by thiorphan (P<0.01, n=3; specific inhibitor). Syncytiotrophoblast-derived microvesicles, isolated from peripheral plasma, demonstrated higher NEP expression in preeclampsia using flow cytometry (P<0.05, n=8). We isolated plasma exosomes using size-exclusion chromatography and showed greater NEP activity in preeclampsia (P<0.05, n=8). These findings show that the placenta releases active NEP into the maternal circulation on syncytiotrophoblast-derived EVs, at significantly greater levels in preeclampsia. NEP has pathological roles in hypertension, heart failure, and amyloid deposition, all of which are features of preeclampsia. Circulating syncytiotrophoblast-derived EV-bound NEP thus may contribute to the pathogenesis of this disease.